2020
DOI: 10.1037/xge0000695
|View full text |Cite
|
Sign up to set email alerts
|

Translating (lack of) memories into reports: Conversion processes in responding to unanswerable questions.

Abstract: When queried about events in the past, a person may face questions that concern details that have been witnessed-answerable questions-and details that have not been witnessed-unanswerable questions. With regard to answerable questions, the person's willingness to answer these questions increases as a function of not only information available about the queried detail itself, but also as a function of contextual information. The present research assesses whether the willingness to report specific-and thus incor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
27
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(29 citation statements)
references
References 66 publications
2
27
0
Order By: Relevance
“…For now, this case remains unsettled. In our previous study (Krogulska et al, 2020) we have shown that specific responses to unanswerable questions are reported with low confidence, a result that can be seen as undermining the false-memory explanation. It is worth noting, however, that a recent study on context effects in recognition by Doss, Picart, and Gallo (2018) does suggest that context reinstatement may lead to experiencing false recollections.…”
Section: Discussionmentioning
confidence: 86%
See 4 more Smart Citations
“…For now, this case remains unsettled. In our previous study (Krogulska et al, 2020) we have shown that specific responses to unanswerable questions are reported with low confidence, a result that can be seen as undermining the false-memory explanation. It is worth noting, however, that a recent study on context effects in recognition by Doss, Picart, and Gallo (2018) does suggest that context reinstatement may lead to experiencing false recollections.…”
Section: Discussionmentioning
confidence: 86%
“…In laboratory experiments, questions become unanswerable whenever a participant is queried about details that were deliberately excluded from the study materials. Thus, the experimenter can ask, for example, about the title of a book that was displayed on a shelf, even though this title was occluded in the slides depicting the queried event (Krogulska, Skóra, Scoboria, Hanczakowski, & Zawadzka, 2020). What links all types of unanswerable questions is the response these questions should be met with.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations